Diversity of fish fauna and water quality at the downstream of Bakun HEP, Batang Balui, Belaga, Sarawak - Liew, Sandra Cindy Chiew Fah (Universiti Malaysia Sarawak, (UNIMAS), 2016)
A study on the fish fauna diversity and water quality was conducted at six stations downstream of Bakun HEP, Batang Balui, Belaga from 20th to 26th August 2015 and from 5th to 11th Novermber 2015. The fishes were caught using monofilament gill nets with different mesh sizes and three-layered net. A total of 364 individuals were caught and dominated by the family Cyprinidae (50.82%), followed by Pangasiidae (46.43%), Bagridae (1.37%), Siluridae (0.82%), and Notopteridae (0.55%). The species from the family Cyprinidae are Cyclochedichthys apogon (7.14%), Osteochilus vittatus (4.95%), Parachela oxygastroides (4.67%), Barbonymus schwanenfeldii (4.40%), and Labiobarbus festivus (4.40%). The distance of sampling stations from the dam to station in upstream of Batang Balui is approximately 3.20 km. Temperature ranged from 26.81 to 27.81 °C, pH with range of 6.32 to 7.47, turbidity from 16.8 NTU to 47.4 NTU, chl-a with range of 0.0032 to 0.036 pg/L and TSS from 16.33 to 30.8 mg/L, and showed significant difference between sampling. The dissolved oxygen ranged from 3.70 to 7.83 mg/L, conductivity with range of 35.0 to 45.0 μS/cm and BOD5 ranged from 1.03 to 6.0 mg/L, and showed no significant difference between sampling periods. The PCA analysis indicated that fishes such as Pangasius macronema, Lobocheilos bo, and Osteochilus vittatus can tolerate the stated range of TSS and turbidity. The present study showed that regulated release of water from Bakun HEP might have impact on fish diversity and water quality at Batang Balui region.